Boromycin has Rapid-Onset Antibiotic Activity Against Asexual and Sexual Blood Stages of Plasmodium falciparum - de Carvalho, Laís Pessanha; Groeger-Otero, Sara; Kreidenweiss, Andrea; Kremsner, Peter G.; Mordmüller, Benjamin; Held, Jana (Frontiers in Cellular and Infection Microbiology, 2022)
Boromycin is a boron-containing macrolide antibiotic produced by Streptomyces antibioticus with potent activity against certain viruses, Gram-positive bacteria and protozoan parasites. Most antimalarial antibiotics affect plasmodial organelles of prokaryotic origin and have a relatively slow onset of action. They are used for malaria prophylaxis and for the treatment of malaria when combined to a fast-acting drug. Despite the success of artemisinin combination therapies, the current gold standard treatment, new alternatives are constantly needed due to the ability of malaria parasites to become resistant to almost all drugs that are in heavy clinical use. In vitro antiplasmodial activity screens of tetracyclines (omadacycline, sarecycline, methacycline, demeclocycline, lymecycline, meclocycline), macrolides (oleandomycin, boromycin, josamycin, troleandomycin), and control drugs (chloroquine, clindamycin, doxycycline, minocycline, eravacycline) revealed boromycin as highly potent against Plasmodium falciparum and the zoonotic Plasmodium knowlesi. In contrast to tetracyclines, boromycin rapidly killed asexual stages of both Plasmodium species already at low concentrations (~ 1 nM) including multidrug resistant P. falciparum strains (Dd2, K1, 7G8). In addition, boromycin was active against P. falciparum stage V gametocytes at a low nanomolar range (IC50: 8.5 ± 3.6 nM). Assessment of the mode of action excluded the apicoplast as the main target. Although there was an ionophoric activity on potassium channels, the effect was too low to explain the drug´s antiplasmodial activity. Boromycin is a promising antimalarial candidate with activity against multiple life cycle stages of the parasite.